Uev1A-Ubc13 promotes colorectal cancer metastasis through regulating CXCL1 expression via NF-кB activation - Wu, Zhaojia (Oncotarget, 2018)
Colorectal cancer is the second most common cause of cancer-related death worldwide. Uncontrolled growth and distant metastasis are hallmarks of colorectal cancer. However, the precise etiological factors and the mechanisms are diverse and still largely unclear. The potential proto-oncogene UEV1A encodes a ubiquitin conjugating enzyme variant, which is required for Ubc13-catalyzed K63-linked poly-ubiquitination of target proteins and the activation of NF-кB, a transcription factor known to be involved in innate immunity, anti-apoptosis, inflammation and cancer. In order to understand the roles of Uev1A in colon cancer progression, we experimentally manipulated the Uev1A level in HCT116 colon cancer cells and found that UEV1A overexpression alone is sufficient to promote invasion in vitro and metastasis in vivo. This process is mediated by NF-κB activation and depends on its physical interaction with Ubc13. No expression of Uev1A was detected in histologically normal human colonic mucosa, but its expression was detected in human colorectal adenocarcinoma, which was closely correlated with nuclear p65 levels, an indicator of NF-κB activation. Uev1A protein was detected in 46% of primary tumors and 79% of metastatic tumors examined. Our experimental data establish that among NF-κB target genes, Uev1A-regulated CXCL1 expression plays a critical role in colon cell invasion and metastasis, a notion supported by the colon adenocarcinoma survey. Furthermore, experimental depletion of Uev1 in HCT116 cells reduces CXCL1 expression, and prevents cell invasion and tumor growth in a xenograft mouse model. These results identify Uev1A as a potential therapeutic target in the treatment of metastatic colorectal cancers.